Detection of human herpesvirus 7 in conjunctival samples collected from individuals recovering from conjunctivitis - Hartwick, Andrew T.E.; Morettin, Christina E.; Harthan, Jennifer S.; Whiteside, Meredith; Shorter, Ellen; Johnson, Spencer D.; Migneco, Mary K.; Olson, Christian K.; Huecker, Julia B.; Than, Tammy; Gordon, Mae O. (Frontiers in Ophthalmology, 2025)
PurposeAlthough it is often reported that adenovirus is the most common etiology for infectious conjunctivitis, a recent multi-center clinical study found that adenovirus was confirmed by polymerase chain reaction in only 16% of cases presenting with acute conjunctivitis. Here, we investigated the hypothesis that a member of Herpesviridae could be the underlying etiology in some non-adenoviral cases of conjunctivitis.MethodsMolecular assays for Herpes Simplex 1 and 2 (HSV-1, HSV-2) and Human Herpesvirus 6A, 6B and 7 (HHV-6A, HHV-6B, HHV-7) were performed on conjunctival samples collected from 18 individuals with acute conjunctivitis and during their recovery in follow-up visits that spanned up to 3 weeks. All samples, obtained from individuals enrolled in a clinical trial evaluating a conjunctivitis treatment, were from eyes that had previously tested negative for adenovirus using polymerase chain reaction (PCR) techniques.ResultsIn total, 160 PCR assays were performed on 40 conjunctival samples. Four of these samples, obtained from four different individuals, tested positive for HHV-7. None of the samples tested positive for HSV-1, HSV-2, HHV-6A or HHV-6B.ConclusionThis data provides further evidence that Human Herpesvirus 7 can be present in the eye, as HHV-7 was detected in a subset of conjunctival samples obtained from individuals recovering from non-adenoviral conjunctivitis. Clinicians should consider non-adenoviral etiologies when managing conjunctivitis that presents as classic ‘pink eye’.